Het Flemish and Dutch Painting : From Van Gogh, Ensor, Magritte and Mondrian to Contemporary Artists - Benvenuti, Feliciano; Calvesi, Maurizio; Fuchs, Rudi H.; Hoet, Jan; Hoozee, Robert; Martens, Luc; Nuis, Aad; Soeting, Margreeth; Wolffram, Dirk Jan; de Schaepdrijver, Sophie; van Os, Henk; Exhibition. Art of the 20th Century, Flemish and Dutch Painting from Van Gogh, Ensor, Magritte, Mondrian to Contemporary Artists. Venezia. Palazzo Grassi Venezia. Museum van Hedendaagse Kunst Gent. 1997-03-16. 1997-07-13 (New York : Rizzoli International Publications, 1997)
This beautiful and comprehensive volume celebrates the connections between Dutch and international modern art. It is based on the exhibition at the famed Palazzo Grassi in Venice, the first in which masterpieces by Belgian and Dutch artists of the last two centuries - Van Gogh, Ensor, Magritte, Mondrian, and many others - are seen together as representative of parallel movements, sharing qualities of elegance, simplicity and rigor. Flemish and Dutch Painting presents the finest examples of the collections of twenty European museums, as well as of premiere private collections, In the fifteenth century the Low Countires were, along with Italy, a leading center of art. Following a chronological path this book is a penetrating survey of how those early developments have influenced and colored the modern age, continuing into Expressionist, Surrealist, and Realist art. In the section illustrating the post-war period, the Cobra group is highlighted, along with an outstanding showing of Marcel Broodthaers. With historical and critical essays by the curators as well as by leading Dutch and Italian art historians, and lavishly illustrated with over 300 color plates, Flemish and Dutch Painting is essential for anyone interested in the art of Belgium and the Netherlands, as well as for readers who want to see beyond the familiar points of view of New York and Paris.
Alechinsky, Pierre ; Van Anderlecht, Englebert ; Appel, Karel ; Armando ; Benner, Gerrit ; van den Berghe, Frits ; Bertrand, Gaston ; Birza, Rob ; Bogart, Bram ; Brands, Eugène ; Broodthaers, Marcel ; Brouwn, Stanley ; Brusselmans, Jean ; Constant ; de Cordier, Thierry ; Corneille ; D'Haese, Roel ; Daniels, René ; Dekkers, Ad ; Delvaux, Paul ; Dibbets, Jan ; van Doesburg, Theo ; van Dongen, Kees ; Dotremont, Christian ; Dumas, Marlene ; van Elk, Ger ; Ensor, James ; Fabre, Jan ; Fernhout, Edgar ; Gentils, Vic ; van Gogh, Vincent ; Henneman, Jeroen ; Hussem, Willem ; De Keyser, Raoul ; Khnopff, Fernand ; Koch, Pyke ; Kruijder, Herman ; Lataster, Ger ; van der Leck, Bart ; Leroy, Eugène ; Lucassen ; Lucebert ; Magritte, René ; Meunier, Constantin ; Minne, George ; Mondriaan, Piet ; Mortier, Antoine ; Panamarenko ; Permeke, Constant ; Raveel, Roger ; Rietveld, Gerrit ; Rops, Félicien ; Schmalzigang, Jules ; Schoonhoven, Jan ; Schouten, Marien ; Servranckx, Victor ; Van Severen, Dan ; Sluijters, Jan ; De Smet, Gustave ; Smits, Jacob ; Spilliaert, Léon ; Struycken, Peter ; Toorop, Charley ; Toorop, Jan ; Tuymans, Luc ; Vantongerloo, Georges ; Vercruysse, Jan ; Verhoef, Toon ; Visch, Henk ; Visser, Carel ; Volten, André ; Westerik, Co ; Wiertz, Antoine ; Willink, Carel ; de Woestyne, Gustave Van ; Wouters, Rik
General Bibliography p. 341-342, Artist Bibliography p. 343-347
biog. p. 321-340
publ. SMAK : zie kast leeszaal
Engels
boek
Keywords: 20ste eeuw; België; Nederland